THE IMPLEMENTATION OF FLEXIBLE WORK ARRANGEMENTS (FWAS) AND ITS IMPACT FOR WORK-LIFE BALANCE OF WOMEN’S WORKFORCE - Awang, Nurulbahiah; Mohd Nadzri , Nazruzila Razniza (I-iECONS e-proceedings, 2023)
Flexible Work Arrangements (FWAs) have become attractive aspects of working models, in response to the changing needs of the modern workforce and advancement in digital technologies especially after the Covid 19 Pandemic. FWAs promote achieving work-life balance (WLB) among workers that limits stress and permits family care. FWAs are consistent with several goals of Sustainable Development Goals (SDG) in achieving gender equality, good health and well-being, decent work and economic growth. International Labour Organization (ILO) also promotes productive work, decent working time and combining work, family and personal life. Hence, this qualitative study which can be considered as action research-based will study the the implementation of (FWAs) in resolving the issue of lower rate of female labor force in employment, challenges encountered by female led households to secure jobs, and accommodate the women in professional occupation. The data is collected from previous studies and reports with regard to the issue of women participation in the workforce and work-life balance. The objective of this research is to examine Malaysian women’s participation trend in the workforce and the extent the FWAs and WLB influence the trend. Additionally, it explores some practices of FWAs in promoting WLB at workplaces both in public and private sectors. Finally, the paper is aimed to investigate the Malaysian existing policies on FWAs in supporting WLB. This research found that Malaysia shows a consistent low participation of women in employment compared to men. Some prevalent reasons resulting in the trend are marriage status, female led households who had difficulty to be in employment, and higher involvement of women in informal sectors. All these reasons are closely associated with difficulty to balance work and life. The implementation of FWAs at selected workplaces either in public or private sectors is positively accepted by both employers and employees but with lack of evidence to confirm the implementation is truly motivated by WLB ideology. Lastly, the Malaysian approach is to remain the implementation of FWAs on a voluntary basis supported by general provisions in the Employment Act 1955 regarding the right to request for FWAs and internal workplace policies to manage the requests.